1994
DOI: 10.1044/0161-1461.2501.09
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Awareness and Written Word Decoding

Abstract: Research has shown that explicit awareness of the speech sound structure of language—that is, phonological awareness—is related to early reading development. The purpose of this study was to assess the effectiveness of four measures of phonological awareness in predicting first grade decoding ability. Measures of phonological awareness at the beginning of first grade were found to be correlated with measures of decoding ability at the end of first grade. Correlations between decoding and phonological awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 32 publications
3
37
0
2
Order By: Relevance
“…The period was approximately six months that encompassed the phonological awareness introduction and the decoding measures. At the end of their study, Swank and Catts (1994) found that phonological awareness measures are strong predictors of decoding. Their study determined that, in discriminating decoders, the particular deletion skill of phonological awareness considered the most effective measure.…”
Section: International Journal Of Linguisticsmentioning
confidence: 97%
See 1 more Smart Citation
“…The period was approximately six months that encompassed the phonological awareness introduction and the decoding measures. At the end of their study, Swank and Catts (1994) found that phonological awareness measures are strong predictors of decoding. Their study determined that, in discriminating decoders, the particular deletion skill of phonological awareness considered the most effective measure.…”
Section: International Journal Of Linguisticsmentioning
confidence: 97%
“…On the other hand, Swank and Catts (1994) investigated the particular effect of phonological awareness on the first graders' decoding ability. The aim of that research was to determine whether the measures of phonological awareness have an impact on predicting the decoding ability of first graders.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%
“…Conscious awareness of the discrete sounds in words and the ability to manipulate sounds in words is critically tied to the development of word recognition and decoding ability in reading (Bradley & Bryant, 1983;Fox. & Routh , 1975;Liberman, Shankweiler, et al, 1974;Stanovich, 1986;Swank & Catts, 1994;Wagner & Torgesen, 1987). In order to acquire accuracy and speed in word recognition while reading, a child must apply knowledge of the sound structure represented by letters and letter combinations seen in print.…”
Section: Phonological Awarenessmentioning
confidence: 99%
“…Swank and Catts [50] make the point that speech-language pathologists are taking a more active role in the identification and remediation of reading disabilities. This fact is reflected in professional journals internationally.…”
Section: Implications For Speech-language Therapistsmentioning
confidence: 99%
“…In reviewing the literature on the topic, Adams [49] concluded that research has clearly demonstrated that explicit training of phoneme awareness is invaluable in achieving the goal of efficient and effective reading. In addition to training studies, predictive studies have clearly supported a relationship between phonological awareness and decoding ability [50].…”
Section: Phonological Awarenessmentioning
confidence: 99%